PENGARUH KOMITMEN DAN MOTIVASI TERHADAP KEPUASAN KERJA AUDITOR INTERNAL - Balantan Balantan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The result of the first hipothesis examination shows that organizational commitment (x1) has no significant impact on internal auditors’ job satisfaction. The result of the second hipothesis examination shows that professional commitment (x2) has no significant impact on internal auditors’ job satisfaction. Then, the result of the third hipothesis examination shows that interaction between organizational commitment and motivation (Zx1-Zx3) does not have an effect on the job satisfaction and last, the result of the fourth hipothesis examination shows that interaction between professional commitment and motivation (Zx2-Zx3) does not have an effect on the job satisfaction which means that here, in this reseacrh, motivation does not represent as a moderating variable.